Size dependent of the effective conductivity of composite with imperfect interfaces - Kien, Nguyen Trung (Vietnam Journal of Mechanics, 2020)
Based on the circle assemblage model, the effective properties of the inclusion with imperfect interface are derived. The equivalent inclusion is incorporated in the Fourier Transform algorithm to determine the effective conductivity of the composite with lowly conducting or highly conducting interface. The size effect is considered for both cases. Numerical results are provided to illustrate the dependence of the effective conductivity on the size of inhomogeneities.